Violence Against Administrators: The Roles of Student, School, and Community Strengths and Cultural Pluralism - Susan D. McMahon; Andrew H. Perry; Taylor Swenski; Kailyn Bare; Jared Hunt; Andrew Martinez; Linda A. Reddy; Eric M. Anderman; Ron Avi Astor; Dorothy L. Espelage; Frank C. Worrell; Christopher M. Dudek (Behavioral Sciences)
Scientific and public attention regarding educator-directed violence has increased over the past 15 years; however, research on violence against administrators is limited. Although school administrators are responsible for school performance and safety, they can be particularly vulnerable to violence from students, teachers, and parents. This study includes 497 pre-K–12th grade school administrators in the United States. A path analysis was conducted to examine the associations between administrator perceptions of student-, school-, and community-level strengths and administrator experiences of verbal/threatening and physical violence. Cultural pluralism, which incorporates student and staff support of cultural differences and honors different voices and cultures in curricula and discussion, was investigated as a moderator of these associations. Results indicate that (a) student strengths are associated with less student verbal/threatening violence against administrators; (b) school strengths are associated with less student and colleague verbal/threatening violence against administrators; and (c) community strengths are associated with less physical violence from students and less verbal/threatening violence from parents against administrators. Cultural pluralism practices significantly moderated the relationship between student strengths and physical violence from colleagues. Findings highlight school practices and policies across the school ecology that are associated with less administrator-directed violence.